Quantitative Assessment of Trace‐Element Contamination in Parenteral Nutrition Components. Issue 8 (13th June 2019) - Olson, Logan M.; Wieruszewski, Patrick M.; Jannetto, Paul J.; Abbott, Jillian C.; McMahon, M. Molly; Nystrom, Erin M.
Abstract: Background: Trace‐element contamination of contemporary parenteral nutrition (PN) components exists in unknown quantities and, in combination with excessive amounts of certain trace elements provided in commercially available adult, pediatric, and neonatal multitrace‐element (MTE) products, could result in eventual accumulation and toxicity. This study aims to quantify trace‐element contamination in components used for PN compounding to further inform recommendations for MTE product reformulation and individualized trace‐element prescribing in PN. Methods: A total of 32 unique components (65 products) available for PN compounding were tested for manganese, chromium, selenium, zinc, and copper contamination, utilizing inductively coupled plasma mass spectrometry. Theoretical adult, pediatric, and neonatal PNs were formulated to assess the impact of macronutrient and micronutrient component doses on PN trace‐element contamination. Results: Trace‐element contamination was detected in 24 (75%) components tested. Chromium and manganese were common, present in 65.6% and 51.5% of all components, respectively. Eight components did not contain detectable trace‐element contamination, most notably sterile water, concentrated dextrose, and lipid emulsion. Manganese contamination in theoretical adult, pediatric, and neonatal PN was 25.18, 9.92, and 1.37 µg, respectively. Chromium contamination was 4.85, 1.5, and 0.28 µg, respectively. Conclusion: Trace‐element contamination was prevalent in components used to compound PN. Our findings support reformulation of adult, pediatric, and neonatal manufactured MTE products to eliminate chromium, decrease manganese, and supply full daily physiologic requirements of selenium, zinc, and copper. Future study is needed to assess the additional contamination that could occur through the compounding and storage processes.